Приповерхностные броуновские моторы, управляемые переменным электрическим полем - Цемик, О.Е.; Чернова, А.А.; Розенбаум, В.М. (Видавничий дім "Академперіодика" НАН України, 2009)
Розглядаються механiзми виникнення направленого обертального i поступального руху наночастинки поблизу поверхнi твердого тiла пiд дiєю змiнного електричного поля. У першому випадку азимутальне обертання полярної частинки забезпечується синхронною модуляцiєю полем мiнiмумiв i максимумiв двох’ямного потенцiалу загальмованого обертання. У другому випадку виникнення направленого руху зарядженої частинки зумовлене флуктуацiями похилої до поверхнi напруженостi електричного поля з нульовим середнiм значенням. Перпендикулярна до поверхнi компонента поля викликає флуктуацiї амплiтуди симетричного перiодичного приповерхневого потенцiалу, тодi як поздовжня компонента забезпечує зсуви частинки вздовж поверхнi. Сумiсна дiя синхронних флуктуацiй симетричного потенцiалу i прикладеного поля приводить до дрейфу частинки вздовж поверхнi. Mechanisms which give rise to the unidirectional rotational and translational motions of a nanoparticle near a solid surface under the action of an alternating electric field are considered. The directed azimuthal rotation of a polar particle arises from the field-induced synchronous modulation of the minima and maxima of the two-well hindered rotation potential. The directed translational motion of a charged particle is caused by fluctuations of the electric field intensity, with its vector being inclined to the surface and having a zero average value. The surface-normal field component induces amplitude fluctuations of the symmetric periodic near-surface potential, whereas the surface-parallel component makes the particle move along the surface. The combined effect of synchronous fluctuations of the symmetric potential and the applied field results in a particle drift along the surface.